The Borrowed Plant Name Stems in the Georgian Gospel - Marine Ivanishvili (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2015)
Cultural historians and archeologists assume as undeniable fact the relationship between the Caucasus and the Middle East already in VI-V centuries BC, especially between the countries of the South Caucasus and the Middle East. As is known with confidence, the Caucasus had been a carrier and propagator, Kulturträger , of the ancient civilization’s achievements in the whole Caucasus. Against this background, it is natural to expect the existence of the traces of the ancient areal contacts in the Kartvelian languages. The phonetic and semantic modifications of the borrowed foreign lexical units are interesting and need to be taken into account for the study of the source language as well as of the borrowing language systems, for clarification of certain scientific facts. In this regard, the Georgian Gospel represents an extremely important source of information. According to the purpose of our research a few basic questions arise: how are the plant names transferred to Georgian Gospel texts – via borrowing, translation, transliteration, loan- words, or replacing by the equivalents of the similar semantics? Are there any Proto-Kartvelian roots among the plant names recorded in Gospels? Are there any examples when with the borrowed vocabulary, we also come across with the Georgian (Kartvelian) synonym forms? Did the borrowed material appear in the Georgian language system by way of Gospel texts translation, or did it exist before? Which cultural, religious motives are related to each plant name in the given context? How are the Kartvelian and borrowed roots distributed (for example, depending on whether the plant grows in Georgia or not)? How adequate are the lexical equivalents and how are the errors explained? - We shall try to answer these questions this time using the examples of the borrowed vocabulary.